Community pharmacists’ skills and practice regarding dispensing fiscalized substances: a cross-sectional survey - El-Dahiyat, Faris; Jairoun, Ammar Abdulrahman; Al-Hemyari, Sabaa Saleh; Shahwan, Moyad; Jairoun, Maimona; Zyoud, Sa’ed H.; Jaber, Ammar Ali Saleh; Faisal Alkhanani, Mustfa; Alhasani, Reem Hasaballah; Ashour, Ahmed M.; Alshehri, Fahad S; Alorfi, Nasser M. (Frontiers in Pharmacology, 2023)
Background: The use of drugs containing fiscalized substances is essential in different medical areas, including pain management, obstetric emergencies, and the treatment of mental disorders. However, due to their potential for abuse and negative health effects, the dispensing of these substances demands pharmacists with the requisite skills and practice. Objective: This study assesses the skills and practices of pharmacy personnel in the United Arab Emirates (UAE) regarding the dispensing of tramadol, a medication containing fiscalized substances, in community pharmacies. Methodology: A cross-sectional study was conducted. Community Pharmacies were chosen via random sampling, and seven well-trained final year pharmacy students visited them and conducted face-to-face interviews. The survey tool covered items highlighting the demographic data of the subjects, and items on the practice and skills regarding dispensing the fiscalized substances. The content validity ratio values of all tool questions were more than 0.78, suggesting acceptable validity and the Cronbach’s α of 0.75 showed as acceptable internal reliability. The primary outcome measures of interest were the skills and practice regarding dispensing Fiscalized substances. Results: A total of 612 pharmacists were recruited in the study. The average practice score was 80%. There was a statistically significant association (p < 0.05) between practices about dispensing fiscalized substances and gender, age group, pharmacy type, work experience, university of graduation, and receiving training on epilepsy and antiepileptic drugs. Conclusion: The results implied that competency and experience are vital factors for the dispensing of tramadol. Contextually, the majority of the pharmacists evidently have the requisite competencies to provide high-quality and proper medical care, with regards to dispensing tramadol, which will minimize drug abuse and medication errors, and assist outpatients to manage their drugs containing fiscalized substances.